Investigation of phase equilibria in polyamorphous systems - Артеменко, Сергей Викторович (Technology audit and production reserves, 2015)
The phase behavior of polyamorphous systems based on modified Van der Waals equation with several critical points is investigated in the article. A model of phase equilibria in binary polyamorphous systems, including liquid-liquid equilibria in one-component systems and evaluation of critical lines in a binary mixture. It is proposed an algorithm for the search of parameters according to the excluded volume for Van der Waals model from density and temperature, which makes it possible to generate more than one critical point in a one-component fluid. To test the hypothesis of the continuity of critical lines in binary mixtures of polyamorphous fluids as an initial approximation used parameters near the critical point of the second component. Calculation of critical curves for binary polyamorphous mixtures confirmed the continuity of the transition from a stable critical point of the first metastable point of the second.